Clinical Laboratory Validation Study of a High Sensitivity Troponin I Assay on a POCT (Point of Care Testing) Device - Fabio Grunspun Pitta; Adriana Caschera Leme; Simone Rodrigues Gomes; Tarsila Perez Mota; Fernanda Vieira Paladino; José Leão de Souza Júnior; Rosemeire de Paula Braz; Thais Cristine Rodrigues Leonel Lamounier; Jéssica Buzin Gomes Ferreira; Carlos Eduardo dos Santos Ferreira (Global Heart)
Background: In Acute Coronary Syndrome without ST-segment elevation, the use of high-sensitivity troponins in rapid protocols is considered the gold standard for diagnostic exclusion/confirmation, in conjunction with clinical stratification. The biggest concern regarding the techniques for troponin evaluation is the time required between collection and delivery of the result. Objective: The objective of the present study is the clinical/laboratory validation of a POCT device for TnI. Methods: In the first phase of the study, samples from 108 patients with known troponin values High Sensitivity Automated Troponin T (TnT) assay from Roche Diagnostics were analyzed for analytical comparability between hs-cTnI of the Analyzer Atellica® vTLi and hs-cTnT Cobas®. The second phase of the study was performed with samples from 51 patients who reported to the emergency department with chest pain for a clinical prospective evaluation and correlation between the hs-cTnI assays of the Analyzer Atellica® vTLi, hs-cTnT Cobas® and Atellica IM 1300. Results: There was a correlation between the POCT Atellica® vTLi and hs-cTnT Cobas® in the serum samples of the control group (r = 0.660, p < 0.0001). Besides, there was a correlation between the Atellica® vTLi, serum hs-cTnT Cobas®, plasma hs-cTnT Cobas®, serum Atellica IM and plasma Atellica IM 1300 platforms in the second phase (p < 0.0001 in all cases). Conclusion: In the present study, the Siemens POCT Atellica® vTLi device showed excellent performance in laboratory validation and correlation with the high-sensitivity TnT assay in different troponin concentration ranges. Given these results, the device can be used in institutions that intend to use a POCT device for 0- and 1-hour chest pain protocols.